Pengetahuan, Kesadaran, dan Kepatuhan: Studi Determinasi Kepatuhan Wajib Pajak di Kecamatan Kemuning Kota Palembang - M Farih Zakka; Sopiyan A.R; Yuli Antina Aryani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to determine the influence of tax attitudes, knowledge and awareness of taxpayers on taxpayers' compliance in paying land and building taxes in Kemuning District, Palembang City. This type of research is descriptive quantitative, which is a study that describes or analyzes the results of a research but is not used to make broader conclusions. The population in this study is Land and Building Taxpayers registered in Kemuning District where the researcher took a population of 15,103 taxpayers in 2024. Sample Withdrawal used is simple random sampling which is calculated using the slovin formula. The results of the study show that partially the attitude of taxpayers does not have a significant effect on taxpayer compliance with the value of t calculated the attitude of taxpayers < t table (0.766<1,660), tax knowledge has a significant effect on taxpayer compliance with the value of t calculating tax knowledge > t table ( 7,835 > 1,660), taxpayer awareness has a significant effect on taxpayer compliance with the value of t calculating taxpayer awareness> t table ( 4,566> 1,660), and simultaneously taxpayer attitude, tax knowledge and taxpayer awareness have a significant effect on taxpayers' compliance with the value of F calculated > F table ( 115,354 > 2.70).